2011
DOI: 10.1108/13581981111106176
|View full text |Cite
|
Sign up to set email alerts
|

Firm size and compliance costs asymmetries in the investment services

Abstract: Purpose -The purpose of this paper is to find out how effectively implemented are measuring approaches to compliance and whether there is a correlation between the measures implementation, financial specialisation and international activity. The authors evaluate if the regulatory framework implies a measure cost asymmetry, depending both on the proportionality principle and on the existence of different supervisors with an heterogeneous set of enforcement rules. Design/methodology/approach -The analysis is bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…As such, we pay attention to the effectiveness of their operations, through adherence to regulations. Third, compliance studies have largely focussed on financial institutions especially in the wake of the global financial crisis (Birindelli and Ferretti, 2013;Gabbi et al, 2011;Sejjaaka, 2005) neglecting other institutions in the same operational environment. Adherence to the public financial regulations enhances society's trust in government and confidence on proper utilisation of the entrusted public resources.…”
Section: Ijse 4311mentioning
confidence: 99%
“…As such, we pay attention to the effectiveness of their operations, through adherence to regulations. Third, compliance studies have largely focussed on financial institutions especially in the wake of the global financial crisis (Birindelli and Ferretti, 2013;Gabbi et al, 2011;Sejjaaka, 2005) neglecting other institutions in the same operational environment. Adherence to the public financial regulations enhances society's trust in government and confidence on proper utilisation of the entrusted public resources.…”
Section: Ijse 4311mentioning
confidence: 99%
“…In turn, scholars address the following aspects in the study reports: implementing the compliance functions in banks (Singh, 2003;Edwards & Wolfe, 2004;Haynes, 2005;Misha, 2016); functional duties and roles of bank compliance officers (Fox, 1999;Meissner, 2018); assessing the compliance risks and their consequences, and compliance risk management (Haddad, 2016 According to analytical studies (Birindelli & Feretti, 2008) on the identification of compliance regularities and, specifically, the comparison of compliance systems used by Italian banks and structural subdivisions of foreign banking groups, the latter seem to pay more attention to compliance issues. Gabbi et al (2011) also factored in the criterion of international activity while cross-checking various groups of financial institutions (banks, insurance and investment companies) and pointed out that financial go-betweens with foreign capital appeared to be more experienced in terms of their ability to assess compliance risks and recognize their danger.…”
Section: Banks' Compliance With Regulatory Requirementsmentioning
confidence: 99%
“…In addition, Gabbi et al (2011) Considering the need to achieve the synergy between the objectives of compliance functions and risk management in banks (Fox, 1999), Edwards and Wolfe (2007) and Mikes (2008) studied certain aspects concerning the significance of compliance with regulatory requirements and the improvement of compliance functions and risk management not only for financial institutions, but also for their stakeholders. Edwards and Wolfe (2007) point out that an important aspect of day-to-day life of any corporate business, especially financial institutions of the United Kingdom, implies the ability to demonstrate the compliance with and competence in regulatory requirements to regulators and other third parties.…”
Section: Banks' Compliance With Regulatory Requirementsmentioning
confidence: 99%
“…Furthermore, large and small banks differ in terms of their business model characteristics, organisational structures and operational processes (Gabbi et al, 2011). Prior empirical research (Protiviti, 2012) has indicated that the company's size could affect IT auditing's effectiveness because, in small organisations, the IT audit unit is often understaffed and the IT auditors' involvement in technological projects is rather limited.…”
Section: The Institutional Contextmentioning
confidence: 99%